PENDAPATAN DAN FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENDAPATAN PETANI KOPI - Fikri Syahputra (STIPER Dharma Wacana Metro, 2020)
Sumatra is an island in Indonesia that contributes to national coffee production. Lampung is an area of the island of Sumatra which is the largest coffee producing province. One of the largest production centers in Lampung is in West Lampung district. The district has a production of 55,628 tonnes of 137,228. Coffee farming activities are the main source of employment for people in the West Lampung region. However, in running the farming, of course there are various problems, such as low productivity, changes in weather, selling prices, and several other contributing factors. This study aims to analyze (1) the income of coffee farmers, (2) the factors that influence the income of coffee farmers. Way tenong sub-district was determined as a research location with the consideration of being one of the coffee producers in West Lampng. The number of research respondents as many as 50 people who as a whole are coffee farmers. To find out the income of coffee farmers using farm income analysis. To determine the factors that influence the income of coffee farmers, multiple linear regression analysis was carried out. The income generated by coffee farmers consists of income on cash costs and on total costs. The amount of each income is Rp. 24,057,845.12 / year and Rp. 23,193,623.79 / year. The R / C value of coffee farming income at cash and total costs were 6.59 and 5.49, respectively. The factors that affect the income of coffee farmers are the number of family members and the amount of production.